Perbawa Musik Low-Fidelity (Lo-fi) dalam Proses Belajar: Studi Takhrij dan Syarah Hadis - Muhammad Farras Syah; Hidayatul Fikra; Wawan Hernawan; Yeni Huriani (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this research is to carry Low-Fidelity (Lo-fi) music in the learning process. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods with contemporary analysis. The fruit of this research is the quality of authentic hadiths and the opinions of scholars on these traditions and the results of research reviews. The conclusion of this study is that music has an influence in building a comfortable and calm atmosphere in the learning process, of course after knowing the law of listening to music. Lo-fi music is a genre of music that is able to create a calm atmosphere and Lo-fi music can be a solution when you want to find peace in your activities, especially in the learning process. This study recommends the presence of Low-Fidelity (Lo-fi) music in the learning process for people who want to increase their choice of learning methods. This study recommends further research on Lo-fi music in improving the learning process using a field study approach.